Implementation and Evaluation of Accounting Information Systems in Manufacturing Company Using System Usability Scale - Sandhiyasa, I Made Subrata; Yanti, Christina Purnama; Hendrawati, Theresia (Journal of Electrical, Electronics and Informatics; Vol 5 No 2 (2021): JEEI (September 2021)DO - 10.24843/JEEI.2021.v05.i02.p05, 2021)
Information systems can facilitate business actors to control and evaluate business reporting effectively and efficiently. Anugrah Sri Jaya is a business engaged in manufacturing. This company still uses a manual recording system which causes several problems, namely frequent errors in calculations and mismatch of inventory stock records with actual conditions. Therefore, the researcher proposes to implement an information system in the accounting process at Anugrah Sri Jaya. From the results of the study, researchers have succeeded in building a web-based accounting information system at Anugrah Srijaya. Information system testing uses the System Usability Scale (SUS) method where the test uses a questionnaire as an assessor and the number of responses is 5 respondents where the respondents from this study are business owners and several employees who will later use this system. From the results of the tests carried out, it can be seen that the average score obtained from the calculation of the System Usability Scale (SUS) is 74.5. Based on the results of the average score, this system can be said to be in the category of acceptance (Acceptable) and on the adjective rating scale, the information system built is rated as excellent.